A co-located solar receiver and thermal storage concept using silicate glass at 1000°C and above: Experiments and modeling in the optically-thick regime. (1st January 2019) - Casati, E.; Lankhorst, A.; Desideri, U.; Steinfeld, A.
Highlights: A co-located solar receiver and thermal energy storage concept is presented. Solar radiation is directly absorbed and stored in a volume of silicate glass. A model coupling Monte Carlo ray-tracing to CFD is developed and validated. A prototype is tested maintaining glass temperatures of 1500 °C for 10 h. Abstract: This work presents the exploratory experimental results of a co-located solar receiver and thermal energy storage (TES) concept based on a pool of molten glass contained in a cavity, serving as solar receiver and TES medium simultaneously. Distinctive features of the system are the direct and volumetric absorption of solar radiation by the semi-transparent glass and a stationary TES medium. Only the charge cycle was studied, without a heat-removal system. Recycled soda-lime-silica (SLS) container glass of various colors was adopted as working medium in a setup tested at the ETH's High Flux Solar Simulator (HFSS). A steady 3D heat transfer model of the experimental apparatus, which couples Monte-Carlo ray-tracing and CFD techniques, was developed and validated against the experimental results. The tests used the HFSS as the only energy source, with maximum radiative fluxes of 1.2  MW m - 2 and power input of 1.5 kW directly absorbed by the glass, which reached measured temperatures of 1300  ° C, while the maximum temperatures –as predicted by the model– exceeded 1500  ° C . Such conditions were maintained for 5 to 10 h and no technical problems were encountered with the containment of the hot glass melt. These preliminary results demonstrate that silicate glasses are effective volumetric absorbers of solar radiation up to temperatures exceeding 1300  ° C .